Relation of fraternities to eductional institutions - Gasser, George W. (My University, 1905)
Introduciton: Whatever conclusion educators, and those who are being educated, may have reached, or lack of conclusion, this fact remains patent; fraternities have entered so vitally and so universally into the educational centers of the nation that their permanence is assured. True it is still a much mooted question in some colleges whether or not college fraternities should be allowed to exist and strong dissensions have arisen; but generally, though often gradually and insidiously, the fraternal organizations have won a permanent home. Excepting the military academies, West Point and Annapolis, where secret societies could not be tolerated by the government, Princeton and Vassar, of all the large eastern colleges, remain with doors closed to Greek letter societies. The typical home of these fraternities is in the eastern college and the time of their inception dates back to early American history. Like a good many other things, both good and bad, fraternities have been swept westward by the strong irresistible sweep of advanced civilization. Simply because fraternities have met strong and determined opposition is, of course, no proof that their dominant influence is evil. Primarily, merely an evidence of diverse opinions. However, the persistent, extended efforts to crush the movement give one a just reason to inquire into and find, if possible, whether or not such opposition is warranted.
Citation: Gasser, George W. Relation of fraternities to eductional institutions. Senior thesis, Kansas State Agricultural College, 1905.
Morse Department of Special Collections
Keywords: Good Influences of Fraternities; Helpful; Theses